Aortic dissection in childbirth as a cause of maternal mortality - T. Yu. Babich; A. N. Sulima; V. V. Voronaya; N. A. Kalinina (Акушерство, гинекология и репродукция)
Introduction. Aortic dissection (AD) is a rare and extremely dangerous pathology in obstetrics and gynecology. AD frequency in pregnant women comprises only 14.5 cases per 1 million subjects and leads to maternal death in 30 % cases. AD is characterized by the difficulty in performing differential diagnostics.Aim: to describe a clinical case demonstrating the difficulties in timely AD diagnostics and treatment during delivery.Materials and Methods. A rare clinical case of asymptomatic AD resulting in death of the woman in labor is presented after assessing the patient medical history, the conclusion of the pathoanatomical examination and the protocol of the mortality review.Results. The presented AD clinical case in labor with subtle clinical symptoms demonstrate the extreme difficulty of timely diagnostics of this pathology for practitioners, which inevitably resulted in maternal mortality.Conclusion. AD during pregnancy and labor is the condition with extremely rare and difficult diagnostics, high probability of maternal and perinatal mortality, which should be known and remembered by obstetrician-gynecologists.